Growth Parameters Related to Productivity in Cassava (Manihot Esculenta Crantz) - Tan, Swee Lian (1980)
Dry matter production and distribution to major plant organs were studied by periodic harvests over 12 months in six varieties of cassava with varying b ranching patterns. Simultaneous studies traced the pattern of branching, leaf size and leaf area development, rates o f leaf production and of nod e weight increase, and leaf life. Total dry matter production depends on leaf area index (LAI) and leaf photosynthetic rate. Measurements by an infra-red gas analyzer on single attached leaves indicated varietal differences in apparent photosynthetic rates. The LAI of three varieties, with high, intermediate and low rates, was altered by leaf and apex clipping. A relationship was found between crop growth rate ( CGR) and LAI, and a possible association between CGR and photosynthetic efficiency. LAI is influenced by canopy characteristics, viz. leaf size, rate of leaf production and leaf life. Leaf production has two components: production rate per apex, and rate of apex production which relates to branching. Root bulking has a lower optimal LAI than CGR, implying competition with dry matter utilization by stems, leaves and stakes. The capacity for b ranching determines LAI but also establishes the potential for top growth and its competitive sink strength . Node weight increased throughout the crop duration, and b ranching both augmented the stem mas s and accelerated leaf production rate through rapid apex increase. Results from leaf and apex clipping suggest that new leaves constituted a very substantial sink.